Changes in Use of Family Planning among the Urban Poor: Evidence from Nairobi Slums. (15th March 2017) - Beguy, Donatien; Ezeh, Alex C.; Mberu, Blessing U.; Emina, Jacques B.O.
Abstract : As urbanization continues unabated in Kenya, the wellbeing of the urban poor ‐ whose majority live in slum settlements ‐ will increasingly drive national development indicators including Vision 2030, SDGs and FP2020 goals. It is therefore central to understand and identify ways to address the poor reproductive health outcomes among poor urban slum populations in the country. Taking advantage of APHRC's NCSS surveys conducted in 2000 and 2012 among a representative sample of slum households across Nairobi, we show that there has been a considerable increase in use of modern contraception among women in Nairobi slums, from 34% in 2000 to 53% in 2012, and a reduction in inequity in access through much higher increases among previously disadvantaged groups. Using decomposition analysis techniques, we show that much of the observed increase is due to behavioral changes in the effect of fertility preferences on contraceptive use; and to compositional changes in woman's education, child survival and exposure to FP information. This may be the result of efforts by the government of Kenya and its development partners to reduce the disparities in uptake and use of FP services through various programs and policies targeting the poor segments of the Kenyan population.